Mobile access to government information and services : trends and federal actions - Weaver, Jordan L. (New York : Novinka/Nova Science Publishers, Inc., 2015)
Today, millions of Americans use mobile devices like smartphones and tablet computers on a daily basis to communicate and obtain information. Further, due to recent technical advances in mobile technology, consumers can use these devices to carry out a broad range of activities that previously required a desktop or laptop computer including shopping, banking, and accessing government services. Given these trends, providing government information and services ""anytime, anywhere, and on any device, "" has become increasingly important, particularly as some mobile users may not have any other mea.
Mobile devices : federal agencies' steps to improve mobile access to government information and services / United States Government Accountability Office -- Digital government : building a 21st century platform to better serve the American people / Office of Management and Budget -- Social networking and constituent communications : Member's use of Twitter and Facebook during a two-month period in the 112th Congress / Matthew Eric Glassman, Jacob R. Straus and Colleen J. Shogan.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: United States. -- Congress; Internet in public administration -- United States; Electronic government information -- United States; Online social networks -- Political aspects -- United States; Administration publique en ligne -- États-Unis.; Réseaux sociaux (Internet) -- Aspect politique -- États-Unis.; Publications officielles électroniques -- États-Unis.; POLITICAL SCIENCE -- Public Affairs & Administration; Online social networks -- Political aspects; Electronic data processing; Electronic government information; Internet in public administration; Mobile computing; United States; Electronic books